Levelling Education Outcomes for Students With Medical and Mental Health Needs. Issue 1 (17th August 2020) - Cave, Leah; Hancock, Kirsten; Jones, Caleb; de Lacy, Deb; Briedis, Trevor; Moffatt, Angelina; Wheatley, Grant
Students' educational and behavioural outcomes can be adversely impacted by the unique challenges posed by chronic health conditions. As some children and adolescents may live with these challenges throughout their education, hospital-based educators play a crucial role in reducing the impacts of health conditions on educational outcomes. This study assessed the extent to which the support provided by the School of Special Educational Needs: Medical and Mental Health (SSEN:MMH, Western Australia) attenuated the negative association between higher absences and lower student outcomes. Administrative education records relating to absences, student behaviour, achievement outcomes, and level of support provided by the SSEN:MMH were used to assess the study questions. Regression models revealed no significant association between higher levels of teaching support and student outcomes after controlling for baseline characteristics. However, the negative association between higher absences and lower academic achievement was lower among students receiving higher levels of liaison. Additional analysis highlighted challenges in evaluating student outcomes, including the finding that most students receiving support missed at least two weeks of school over a year but received less than the equivalent of two days of teaching support, suggesting that the available measures were not sensitive to the level of teaching support provided. Together, the findings of this study suggest that liaison services informing schools about the educational needs of students are an important tool for supporting students academically and that the process of supporting students with chronic health conditions is not a simple task given the varying complexity of student needs and behaviours.